Between the office tower and the private neighborhood : Urban grids in "Nuestro modo de vida" by Fogwill - Guerra, Juan José (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The aim of this paper is to analyze the configuration of urban space in Nuestro modo de vida (2014) by Fogwill. In a novel that echoes the primacy of flow as the main way of moving around the contemporary city, we are particularly interested in evaluating the way in which its characters move around an urban space that appears fragmented. The linearity proposed by highway trips seems to guarantee the safety of transit through the city for characters who remain sheltered from a certain “fondo de terror” that underlies the story.